Estimate of stochastic model parameter of exchange rate using machine learning techniques. (22nd July 2019) - Mostafa, El Hachloufi; Hamza, Faris; Mohammed, El Haddad
In this paper, we present a new approach for estimating the stochastic model parameter of exchange rate using genetic algorithms and neural networks. This approach takes in consideration the minimisation of exchange rate risk that is measured by the conditional value at risk CVaR in the estimation procedure of this parameter. The objective of this approach is to provide a tool of decision for the exchange market managers.